2021
DOI: 10.1097/gox.0000000000003769
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Viscoelastic Tests to Predict Flap Thrombosis: A Systematic Review

Abstract: Background: Flap thrombosis is a rare but devastating complication in microsurgery. Preoperative identification of patients at increased risk for microvascular thrombosis remains challenging. Viscoelastic testing (VET) provides a comprehensive evaluation of the clotting process and can effectively identify hypercoagulability. However, the utility of VET in microvascular reconstruction remains unclear. Methods: A systematic review of the association between VET and pedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Existen varias series de casos que han mostrado la capacidad predictiva de las pruebas viscoelásticas de trombosis del colgajo. Sin embargo, aún faltan estudios con mayor número de pacientes, dada la baja incidencia de esta complicación, que actualmente están en torno al 5% [18], [19].…”
Section: Predicción De Trombosis De Colgajounclassified
“…Existen varias series de casos que han mostrado la capacidad predictiva de las pruebas viscoelásticas de trombosis del colgajo. Sin embargo, aún faltan estudios con mayor número de pacientes, dada la baja incidencia de esta complicación, que actualmente están en torno al 5% [18], [19].…”
Section: Predicción De Trombosis De Colgajounclassified
“…Recent studies showed that VET was able to predict flap thrombosis in patients undergoing maxillofacial surgery [ 26 , 27 ]. However, these studies focused only on hypercoagulability assessed with VET.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8 Thromboelastography provides a rapid assessment of hemostasis of a whole blood sample and can predict risk of thrombosis and bleeding. [9][10][11] The technology may be beneficial for patients with cirrhosis experiencing bleeding, thrombosis, or undergoing invasive procedures or surgery. 1,7,12,13 A recent prospective cohort study found that the thromboelastography marker of clot stability (maximum amplitude) could accurately distinguish between cirrhosis patients with major, life-threatening procedure-related bleeding and those who were not bleeding or had minor bleeding, whereas a low platelet count could not distinguish between any procedure-related bleeding (major or minor) and no bleeding.…”
mentioning
confidence: 99%